1995
DOI: 10.1074/jbc.270.17.9856
|View full text |Cite
|
Sign up to set email alerts
|

Localization of I2-Imidazoline Binding Sites on Monoamine Oxidases

Abstract: Imidazoline binding sites (IBS) were proposed to be responsible for some of the pharmacological and therapeutic activities of imidazoline and related compounds and have been classified into two subtypes, I1BS and I2BS. Convergent studies attribute a role in central blood pressure regulation to the I1BS. In contrast, the function of I2BS remains unknown. In the present study, by combining biochemical and molecular biology approaches, we show that 1) microsequencing of I2BS purified from rabbit kidney mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
140
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 26 publications
7
140
0
Order By: Relevance
“…Several studies have demonstrated that the I 2 -imidazoline site is a MAO regulatory site (Tesson et al, 1995;Tesson & Parini, 1991). The results obtained with microdialysis techniques suggest that 2-BFI may act as a MAO inhibitor .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Several studies have demonstrated that the I 2 -imidazoline site is a MAO regulatory site (Tesson et al, 1995;Tesson & Parini, 1991). The results obtained with microdialysis techniques suggest that 2-BFI may act as a MAO inhibitor .…”
Section: Discussionmentioning
confidence: 66%
“…This protocol for clorgyline treatment downregulates non-adrenoceptor [ 3 H]-idazoxan binding sites in the rat brain (Olmos et al, 1993). Since several authors have suggested that I 2 -imidazoline sites are MAO regulatory sites (Tesson et al, 1995;Tesson & Parini, 1991) we also evaluated in vitro the eect of clorgyline in addition to an imidazoline, on the LC.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Therefore, it is uncertain if the cloned I 1 site is actually a true receptor (Piletz et al 2000a). I 2 sites are somewhat better understood, and have been physically linked to monoamine oxidases (Tesson et al 1995). In addition, there are at least two subtypes of I 2 sites that exhibit biphasic binding curves (Eglen et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…125 I]AZIPI and do not inhibit [ 3 H]idazoxan binding to the heterologously expressed enzymes (9). Thus the binding of these compounds likely involves a site on the enzymes distinct from the substrate recognition site.…”
Section: Discussionmentioning
confidence: 99%
“…Partial amino acid sequencing of a purified rabbit kidney imidazoline binding protein revealed high sequence similarity to monoamine oxidases of other species whose sequences are known, and heterologous expression of human MAO-A or MAO-B indicates that both isoforms recognize the imidazoline, [ 3 H]idazoxan, a ligand commonly used to identify imidazoline binding sites in various tissues (9). However, the affinity of the enzymes for [ 3 H]idazoxan following expression in Saccharomyces cerevisiae is 10 -50-fold lower than that expected for the imidazoline binding site (9), and some members of the imidazoline binding protein family do not recognize this radioligand when evaluated in their natural environment within the cell (10).…”
mentioning
confidence: 99%